Literature Review: Evidence of Day-of-the-Week Effect in Cryptocurrency Market - Kie, Tan Sze; Jiun, Ricky Chia Chee (Journal of Accounting, Business and Management (JABM), 2024)
This study provides a comprehensive analysis of the anomaly of day-of-the-week effect found in cryptocurrency market. Its primary objective is to synthesize existing literature and offer an overview of the current understanding of this phenomenon, while identifying trends and research gaps. A systematic literature review was conducted across three major databases—Emerald Insight, Science Direct, and JSTOR—using the keywords "cryptocurrencies" or "cryptocurrency" and "day of the week effect." After applying inclusion and exclusion criteria, 10 relevant articles were identified, and an additional 5 studies were included through manual data extraction from included studies, resulting in a total of 15 articles analyzed. The findings reveal increasing evidence of dayof-the-week effect in cryptocurrency markets, with specific days exhibiting significantly higher or lower returns. However, the exact patterns and underlying drivers of this effect remain underexplored. This review emphasizes the need for additional research to gain a deeper understanding of the time-based anomalies in cryptocurrency price fluctuations and their effects on investors and policymakers.